PERCEIVED ALTERNATIVES OPPORTUNITY SEBAGAI PEMODERASI PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN CONSIGNMENT PT MATAHARI DEPARTEMENT STORE TBK. CABANG BENGKULU - Occy Rahmada Ningsih; Sugeng Susetyo; Paulus Suluk Kananlua (Unib Press Universitas Bengkulu, 2020)
The purpose of this study is to determine the Perceived Alternatives Opportunitiy as moderating the effect of job satisfaction on turnover intention in employee consignment in PT. Matahari Departement Store Tbk Bengkulu City. This research use quantitative approach by using primary data collected by questionnaire. The sample is consignment employees at PT. Matahari Departement Store Tbk Bengkulu City for amount 169 person taken using the sencus method. The data processing technique of this study used Statistical Package For Social Science (SPSS) software version 16.0. The analysis which is used including validity test and reliability test. The results of this study; 1) job satisfaction has a negative effect on Turnover Intention. 2) Job Satisfaction and Perceived Alternatives Opportunity affect Turnover Intention. 3) Perceived Alternatives Opportunity moderate the effect of Job Satisfaction on Turnover Intention.Keywords : Job Satisfaction, Perceived Alternatives Opportunity, TurnoverIntention